International Professorial Chair 2016 International Summer School: Connecting the Best for Education: Icosaedro Proposal: III Towards the Overcoming of the Condition of Educational Extra-Age, a Step for the Construction of Peace: Evaluation of “Back to School” Program - Ruiz-Gómez, Linda Johana; Villamizar, Judith; Molano-Camargo, Frank; Bocanegra-Millán, Andrés M.; Peralta-Ardila, María del Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The following article seeks to analyze the educational program ―Volver a la Escuela‖ (back to school), created by the SED (Secretaría de Educación Distrital, by its Spanish acronym), to know how it works in our country and understand which are its strengths and weaknesses bearing in mind the different war sceneries, armed conflict, poverty, displacement, among others, which have limited the access of vulnerable population to primary and high school in our country. At first, this article presents available information on extra-age condition in Colombian population and the program ―Volver a la escuela‖. Secondly, statistics data related to the program, the teachers, the psychosocial support group, the students during their learning process, guidelines of the program, workshops and elements related to its infrastructure are presented. Thirdly, some interviews provided by teachers and students involved in the program are displayed, whose experiences rescue important clues of the development, possibilities and limitations of this program. Fourthly, a political and public strategy is proposed as a contribution for the implementation of substantial measures of the extra-age status. These measures have the objective to improve the quality of education, proposing intercultural inclusion activities which promote participation, minimize the inequality gap, and especially invite students to finish their basic educational process. Finally, a group of proposals and recommendations to improve the quality of the program is exposed, from an educational, social and cultural perspective which guarantees the right of education for all the Colombians.